Development of Digital Technologies for the Arctic Zone of the Russian Federation - GOLUBEV, Sergei Sergeevich; EFREMOV, Andrey Aleksandrovich (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The modern problems and specifics of developing digital technologies for the Arctic zone of the Russian Federation are analyzed in the article. General approaches to the management of industrial digital technologies for the Arctic are also considered. The problems of the technical equipment operation in the Arctic zone are associated with its severe climate. Digital technologies are more resistant to low-temperature operation in the Arctic. The risks of introducing digital technologies in the Arctic zone are associated with its insufficient innovative potential, high resource intensity, and low efficiency of extractive activities, as well as underdeveloped infrastructure. At the same time, digital technologies contribute to a more active and efficient resolution of these problems. The strategic areas of introducing digital technologies in the Arctic zone are associated with more intensive development of information support systems, digital communications technologies, digital modeling, and new digital technologies. The modern aspects of developing digital technologies in the Arctic are covered in the article. Much attention is paid to the formation and implementation of the interdepartmental integrated target program ‘Arctic Technologies’, which includes digital technologies in lighting systems in the Arctic region, communication and navigation systems, autonomous power supplies and energy storage systems, transport systems, as well as in infrastructure facilities and means of extreme medicine and ecology.